The Influence of Resilience and Workload on The Intention to Stay Among Nurses at Bunda Medika Jakabaring Hospital, South Sumatra Province - Andra Kurnianto; Rian Andriani; Oke Andikarya (Jurnal Wacana Ekonomi, 2025)
The demand for healthcare personnel continues to increase. Hospitals must sustain the continuity of healthcare workers who recognize their own existence as essential actors in the hospital health service system to prevent a decline in performance and the decision to leave the hospital. The intention to stay refers to nurses' desire to continue working at their current hospital. The intention to stay is crucial for the continuity of a hospital organization and is influenced by several factors. This research aims to analyze the effects of resilience and workload on nurses' intention to stay at the hospital. The results indicate that resilience has a significantly positive direct impact, while workload has a significantly negative direct impact on nurses' intention to stay. Resilience and workload together have a significant effect on nurses' intention to stay. Emphasizing that, in predicting this intention, it is necessary to consider not only the workload's heaviness but also the nurses' resilience, or mental endurance, in facing their tasks.